Atrioventricular 2:1-conduction via an accessory pathway during left atrial flutter unmasking WPW syndrome: a case report. Issue 7 (28th June 2022) - Huttelmaier, Moritz Till; Herting, Jonas; Fischer, Thomas Horst
Abstract: Background: Implantable cardioverter defibrillators (ICDs) are most effective in treating sudden cardiac death. However, accurate diagnostic workup of broad complex tachycardia is crucial to ensure correct indication for ICD treatment and to avoid unnecessary invasive treatment and device-associated morbidity. Case summary: We present a case of atypical atrial flutter with 2:1 atrioventricular (AV) conduction via a left-posterior accessory pathway (AP), leading to the diagnosis of Wolff-Parkinson-White (WPW) syndrome. Upon admission, the 72-year-old patient showed a regular broad complex tachycardia with superior axis and positive concordance in precordial leads, suggestive of either ventricular tachycardia (VT), antidromic AV re-entrant tachycardia (AVRT), or supraventricular tachycardia with antegrade conduction via a left-posterior AP. Interrogation of the two-chamber ICD, which was very likely implanted unjustified in a peripheral clinic before, revealed atrial flutter with 2:1 AV conduction. Remarkably, after the restoration of sinus rhythm, no classic echocardiogram (ECG) criteria for preexcitation syndrome were detected. An invasive electrophysiological study proved the diagnosis of a bidirectionally conducting, left-posterior AP, which was successfully ablated. Discussion: Differential diagnosis of broad complex tachycardia with superior axis and positive concordance of chest leads consists of i) VT with a left ventricular exit at the posterior mitral annulus, ii) antidromic AVRT involving a left-posterior AP, and iii) supraventricular tachycardia predominantly conducted via a left-posterior AP. The absence of classic ECG criteria for preexcitation syndrome does not rule out AP sufficiently, highlighting the importance of minimal surface-ECG preexcitation criteria. In the case of detection of minimal surface-ECG preexcitation criteria, administration of adenosine rules out or proves the existence of an AP noninvasively and cost-effectively.